1981
DOI: 10.1055/s-0038-1653426
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Factor VIII Complex Activities During the Production of a Clinical Intermediate Purity Factor VIII Concentrate

Abstract: SummarySamples taken at various stages of preparation of intermediate purity factor VIII concentrate were assayed for factor VIII coagulant activity (VIII:C), factor VIII coagulant antigen (VIIIC: Ag) and factor VIII related antigen (VIIIR: Ag). The antigen results were used to assess mechanical loss during fractionation as these markers are relatively stable. In contrast VIII:C is sensitive to both mechanical and inactivation losses.The major loss of factor VIII occurred during the cryoprecipitation and extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Results from the preliminary study suggested that the loss of VIII:C activity previously observed over product finishing [4] might be almost fully explained by a citrateinduced inactivation of VIII:C. Similar inactivation behaviour had been observed in plasma [13,14] with one suggestion being that the presence of calcium ions is essential for VIILC stability. Therefore a number of for mulations were examined in which the concentration of ionised calcium was controlled by the addition of calcium chloride to factor VIII solutions at different citrate con centrations.…”
Section: Comparison Of Different Formulationssupporting
confidence: 62%
See 4 more Smart Citations
“…Results from the preliminary study suggested that the loss of VIII:C activity previously observed over product finishing [4] might be almost fully explained by a citrateinduced inactivation of VIII:C. Similar inactivation behaviour had been observed in plasma [13,14] with one suggestion being that the presence of calcium ions is essential for VIILC stability. Therefore a number of for mulations were examined in which the concentration of ionised calcium was controlled by the addition of calcium chloride to factor VIII solutions at different citrate con centrations.…”
Section: Comparison Of Different Formulationssupporting
confidence: 62%
“…There have been few reports investigating the points of VIIFC loss during routine manufacturing pro cesses: however, the fact that significant loss of VIIFC can occur over the sterile filtration or finishing procedures has been appreciated for some time [21][22][23]. This was believed to be largely due to the retention of factor VIII on the filter itself, but the development of immunoassays lead instead to the suggestion that some form of inacti vation may provide the predominant mechanism of loss [4]. Previous studies concerning VIIFC inactivation dur ing processing have tended to concentrate on various types of proteolytic degradation [24], whereas our prelim inary stability study drew attention to the importance of product formulation and especially to the role of citrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations